Efficient design optimization of variable-density cellular structures for additive manufacturing: theory and experimental validation. Issue 4 (20th June 2017) - Cheng, Lin; Zhang, Pu; Biyikli, Emre; Bai, Jiaxi; Robbins, Joshua; To, Albert
Abstract : Purpose: The purpose of the paper is to propose a homogenization-based topology optimization method to optimize the design of variable-density cellular structure, in order to achieve lightweight design and overcome some of the manufacturability issues in additive manufacturing. Design/methodology/approach: First, homogenization is performed to capture the effective mechanical properties of cellular structures through the scaling law as a function their relative density. Second, the scaling law is used directly in the topology optimization algorithm to compute the optimal density distribution for the part being optimized. Third, a new technique is presented to reconstruct the computer-aided design (CAD) model of the optimal variable-density cellular structure. The proposed method is validated by comparing the results obtained through homogenized model, full-scale simulation and experimentally testing the optimized parts after being additive manufactured. Findings: The test examples demonstrate that the homogenization-based method is efficient, accurate and is able to produce manufacturable designs. Originality/value: The optimized designs in our examples also show significant increase in stiffness and strength when compared to the original designs with identical overall weight.